Betulinic acid lowers lipid accumulation in adipocytes through enhanced NCoA1-PPARγ interaction - Al-Mutary Mohsen G; Gasem Mohammad Abu-Taweel; Rajakrishnan Rajagopal; Kim Sun-Ju; Hak-Jae Kim; Young Ock Kim; Ramzi A. Mothana; Shine Kadaikunnan; Jamal M. Khaled; Nasir A. Siddiqui; Adnan J. Al-Rehaily (Elsevier, 2019)
Background: Investigation for a naturally occurring anti-obesity drug has become the need of society all over the world. Betulinic acid (BA) is a lupane-type pentacyclic triterpene and is sourced from various organisms. This high potential biologically active molecule is reported to have anti-obesity effect. In this study, we report the molecular mechanism of action of BA that underlies anti-obesity activity and also an improved method of its isolation common teak tree. Methods: Mouse pre-adipocyte cells were used to develop hyperlipidemic conditions in vitro. Change in expression of genes associated to adipogenesis was checked using quantitative real-time PCR (qPCR). Co-factor specificity of PPAR gamma was analyzed through immune precipitation and immunoblot. Results: Betulinic acid was found to be effective in reducing the lipid content in 3T3L1 cells. Level of PPAR gamma and LXR alpha was reduced in connection to reduced adipogenesis. Change in steroid responsive co-activators (SRCs) during BA treatment proved that the compound can impart profound change in co-factor selectivity, which is crucial in determining the activity profile of PPAR gamma. BA treatment enhanced the SRC-1 interaction with PPAR gamma while reducing the levels of SRC-3. Conclusion: Present study has proved that betulinic acid, a promising candidate in anti-obesity drug development, has potential in regulating the activity of PPAR gamma through co-factor modulation. Keywords: Adipogenesis, Betulinic acid, NMR, PPAR gamma, Tectona grandis